A robust method for simultaneous measurement of serum 25(OH)D, 1, 25(OH)2D, and 24, 25(OH)2D by liquid chromatography‐tandem mass spectrometry with efficient separation of 3‐epi analogs, 23R, 25(OH)2D3, and 4β, 25(OH)2D3. (16th December 2021) - Wang, Danchen; Yu, Songlin; Zhang, Qi; Cheng, Qian; Xie, Shaowei; Zhang, Yuanyuan; Guo, Xiuzhi; Zou, Yutong; Yin, Yicong; Yu, Jialei; Li, Honglei; Xia, Liangyu; et al.
Abstract: Background: This study aimed to establish a robust, simple method to detect 25‐hydroxyvitamin D3 (25(OH)D3 ), 25‐hydroxyvitamin D2 (25(OH)D2 ), 1, 25‐dihydroxyvitamin D3 (1, 25(OH)2 D3 ), 1, 25‐dihydroxyvitamin D2 (1, 25(OH)2 D2 ), 24, 25‐dihydroxyvitamin D3 (24, 25(OH)2 D3 ), and 24, 25‐dihydroxyvitamin D2 (24, 25(OH)2 D2 ) simultaneously with efficient separation of 3‐epi 25(OH)D3, 3‐epi 24, 25(OH)2 D3, 23R, 25(OH)2 D3, and 4β, 25‐dihydroxyvitamin D3 (4β, 25(OH)2 D3 ) by liquid chromatography‐tandem mass spectrometry (LC‐MS/MS). Method: This method was validated according to procedures established by Clinical and Laboratory Standards Institute (CLSI) and then applied in healthy population to determine the distribution of the vitamin D metabolites by LC‐MS/MS. Results: The total‐run CV% of 25(OH)D3, 25(OH)D2, 24, 25(OH)2 D3, 24, 25(OH)2 D2, 1, 25(OH)2 D3, and 1, 25(OH)2 D2 were 6.30%–8.40%, 5.00%–8.40%, 5.90%–9.00%, 5.60%–9.00%, 5.60%–8.00%, and 7.00%–9.70%, respectively. The linearity correlation coefficients r of these six vitamin D metabolites were >0.99. The matrix effects of 25(OH)D3, 25(OH)D2, 24, 25(OH)2 D3, 24, 25(OH)2 D2, 1, 25(OH)2 D3, and 1, 25(OH)2 D2 were 90.6%–103.3%, 97.3%–106.3%, 90.7%–106.3%, 100.7%–114.5%, 97.9%–104.6%, and 97.0%–111.0%. The trueness values of 25(OH)D3, 25(OH)D2, and 24, 25(OH)2 D3 were 93.8%–103.0%, 101.0%, and 96.3%–100%, respectively. Conclusion: This study successfully established an efficient, accurate, robust method for simultaneous measurement of serum 25(OH)D, 1, 25(OH)2 D, and 24, 25(OH)2 D by LC‐MS/MS with efficient separation of 3‐epi analogs, 23R, 25(OH)2 D3, and 4β, 25(OH)2 D3 .